Racionalidade pedagógica democrática e a racionalidade pedagógica democratizante nas comunidades de aprendizagem cooperativa: trabalho de colaboração e trabalho colaborativo
This report seeks to understand the role of the public school as a pedagogical, social, cultural and political space, grounded on democratic principles and a logic of cooperative management of school environments. This approach is understood not only as being shaped by contributions from pedagogy, but also as a response to the political, economic, cultural and social transformations of the contemporary world. The analysis starts from a pedagogical rationality that values communication as an educational process, reflecting the ideologies that shape educational policies and classroom dynamics and the articulation of democratic and democratising pedagogical rationality. These orientations are important for developing the relationship between teachers and students in the construction of teaching-learning contexts. Within this framework, a teaching unit was developed entitled "Me, Us, the Class, the School - An Artistic Exploration" was developed in the Drawing A subject. The proposal, centred on reflecting on the role of the school in students' lives, focused on the development of social skills such as communication and cooperation. There were explored through concepts with different pedagogical implications, both through cooperative work and collaborative work between peers.